English Language Student Teachers’ Pedagogical Beliefs: Susceptibility to Change and Sources of Change - Glušac, Tatjana LJ.; Pilipović, Vesna B. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Pedagogical beliefs comprise assumptions about different elements of education, and, hence, impact the entire pedagogical activity of the teacher. Relevant literature suggests it is vital to discover student teachers’ beliefs, but it provides contradicting evidence regarding the effects that teacher preparation programs have on changing students’ beliefs. This paper aims at discovering whether student teachers’ beliefs alter in response to their attendance in different teacher-preparation courses, as well as the sources of that change. The paper is based on a mixed-model inquiry for whose purpose a Likert-scale questionnaire was composed and a semi-structured interview conducted. The sample included 11 EFL postgraduate student teachers from Serbia. The gathered findings indicate a few statistically significant changes on the group level, while the results on the individual level reveal a variety of significant changes. Field practice was shown to have the greatest impact on changing student teachers’ pre-existing beliefs, closely followed by a theoretical-practical course they attended, whereas the least impactful was a purely theoretical course.
Keywords: English language; change of pre-existing beliefs; pre-existing beliefs; student teachers’ pedagogical beliefs